Chronic kidney disease in patients with type 2 diabetes: new targets of medicine action - N. P. Trubitsyna; N. V. Zaitseva; A. S. Severinа; M. S. Shamkhalova (Сахарный диабет)
Diabetes mellitus type 2 (DM2) is socially important disease, becoming non-infectious epidemic due to increasing prevalence. Chronic kidney disease (CKD) is one of the most common diabetic complications. Kidney injury signs and/or estimated glomerular filtration rate (eGFR) decrease are seen in 40-50% of patients with DM2. Three groups of factors are considered to be the basis of CKD development and progression in DM2: metabolic, hemodynamic, inflammation and fibrosis. Existing drugs that are used in patients with CKD and DM2 first of all target hemodynamic and metabolic disturbances, but their action against inflammation and fibrosis is indirect. Hyperactivation of mineralocorticoid receptors (MR) is considered as one of the main trigger factors of end-organ damage in patients with DM2 due to inflammation and fibrosis. Development of selective nonsteroidal MR antagonists (MRA) as a new class of medications is directed to demonstrate positive effects from blocking this pathophysiological pathway of CKD development and overcome the steroidal MRAs’ shortcomings. Hence pathophysiological hyperactivation of MR with subsequent inflammation and fibrosis in patients with CKD in DM2 is considered a promising therapeutic target for the new drugs with cardionephroprotective effect.